Branched short-chain fatty acids modulate glucose and lipid metabolism in primary adipocytes. (1st October 2016) - Heimann, Emilia; Nyman, Margareta; Pålbrink, Ann-Ki; Lindkvist-Petersson, Karin; Degerman, Eva
ABSTRACT: Short-chain fatty acids (SCFAs), e.g. acetic acid, propionic acid and butyric acid, generated through colonic fermentation of dietary fibers, have been shown to reach the systemic circulation at micromolar concentrations. Moreover, SCFAs have been conferred anti-obesity properties in both animal models and human subjects. Branched SCFAs (BSCFAs), e.g., isobutyric and isovaleric acid, are generated by fermentation of branched amino acids, generated from undigested protein reaching colon. However, BSCFAs have been sparsely investigated when referring to effects on energy metabolism. Here we primarily investigate the effects of isobutyric acid and isovaleric acid on glucose and lipid metabolism in primary rat and human adipocytes. BSCFAs inhibited both cAMP-mediated lipolysis and insulin-stimulated de novo lipogenesis at 10 mM, whereas isobutyric acid potentiated insulin-stimulated glucose uptake by all concentrations (1, 3 and 10 mM) in rat adipocytes. For human adipocytes, only SCFAs inhibited lipolysis at 10 mM. In both in vitro models, BSCFAs and SCFAs reduced phosphorylation of hormone sensitive lipase, a rate limiting enzyme in lipolysis. In addition, BSCFAs and SCFAs, in contrast to insulin, inhibited lipolysis in the presence of wortmannin, a phosphatidylinositide 3-kinase inhibitor and OPC3911, a phosphodiesterase 3 inhibitor in rat adipocytes. Furthermore, BSCFAs and SCFAs reduced insulin-mediated phosphorylation of protein kinase B. To conclude, BSCFAs have effects on adipocyte lipid and glucose metabolism that can contribute to improved insulin sensitivity in individuals with disturbed metabolism.